Pengaruh Ukuran Kantor Akuntan Publik, Leverage, dan Audit Tenure Terhadap Integritas Laporan Keuangan - Krisnhoe Sukma Danuta; Siti Muntahanah; Suripto Suripto; Tri Handayani; Santi Suciningtyas (Majalah Imiah Manajemen & Bisnis, 2022)
This study aims to see the effect of KAP size, leverage, and audit tenure on the integrity of financial reports in property and real estate companies listed on the Indonesia Stock Exchange in 2017-2020. The sampling method uses a purposive sampling method which result 21 companies as samples. Panel regression data used for analysis of the research with the help of Eviews. The results showed that KAP size had a significant negative effect on the integrity of financial statements. Meanwhile, leverage and audit tenure have a significant positive effect on the integrity of financial statements